Band Alignment at n-GaN/Electrolyte Interface Explored by Photo-Induced Offset of Open-Circuit Potential for Efficient Water Splitting. (25th April 2017) - Imazeki, Yuuki; Iwai, Yohei; Nakamura, Akihiro; Koike, Kayo; Sato, Shin-ichiro; Ohshima, Takeshi; Fujii, Katsushi; Sugiyama, Masakazu; Nakano, Yoshiaki
Abstract : The band alignment at the interface between an electrolyte and n-GaN photoanode was investigated by observing open-circuit potential (OCP) of the GaN as a function of irradiated Xe-lamp intensity. The OCP drifted to negative values almost linearly with respect to the logarithm of light intensity, similarly to the behavior of open-circuit voltage in solar cells. For the smaller light intensity than 10 -2 mW/cm 2, OCP value was less dependent on light intensity and it was sensitive to both the surface treatment of GaN and the surface damage which was introduced intentionally prior to the photoelectrochemical analysis by the irradiation of accelerated Ar atoms, high-energy electrons and γ-ray. The relationship between OCP and light intensity can be obtained without modifying the surface by photocurrent and it would be a good indicator how the surface treatment of a photoelectrode affects the photocatalytic activity.